HUMAN RESOURCES AS A DETERMINING FACTOR FOR THE COMPETITIVENESS OF THE MSME SECTOR - Lisa Sarinah (Jurnal Info Sains : Informatika dan Sains, 2022)
The human element is the most significant of all the components that go into making up an organization, and as a result, it is also the most difficult to govern. This is due to the fact that everyone's ideas and points of view are quite distinct from one another. In the same way, organizational culture enables members of a company to develop positive working relationships among themselves and collaborate in an organizational climate that is beneficial to them and, in turn, to the dynamics of the organization, the organizational structure guides the way people act, providing the formalism and complexity of the process. The purpose of the research proposal is to shed light on how the performance of human resources gives quality to processes and consequently results in actions that encourage companies to be more efficient; it is dependent on the human resource strategy that members of a company are a competitive factor and strengthen the position of the company in the market, in this case MSMEs.